Academic stress and coping in high school adolescents - Pillai, Jitesh; Jose, Soumya; A. Velukutty, Bijumon; Riyaz, A. (International Journal of Contemporary Pediatrics, 2023)
Background: Education stress is widely recognized as one of the most important precursors leading to depression in adolescent life. This study explores the prevalence of academic stress among high school going adolescents, contributing factors and the coping strategies used by students. The finding of this study aids the teaching institutes to better the understanding of the stress due to present teaching methods. Methods: A cross-sectional study was conducted in 2020 at both private and government schools of Kozhikode, Kerala. 371 students were selected randomly. A questionnaire was developed incorporating educational stress scale for adolescent (ESSA), academic stress scale (ASC) and simplified coping styles questionnaire (SCSQ). Results: 70.8% students have minimal stress, 25.8% moderate stress, 0.002% high stress, 0.02 did not have stress. Female participants experienced more stress compared to male participants (p value=0.04). Participants with less educated father (p value <0.001) and with less educated mother (p value <0.001) experienced more stress. Last year final exam grade (p value=0.005) and parental pressure (p value=0.008) were important factors contributing to stress. With regard to deployment of coping strategies 0.5% never used any coping strategies, 53.6% students used coping occasionally, 45% often used coping, 0.8% used coping frequently. Conclusions: Most of the children studying in high school have minimal to moderate stress. The main factors that contribute to stress more are female gender, low parental education level, and poor final exam grade. Positive association for factors like parental pressure with increasing age was present. Most of the students used different coping strategies to cope with the education stress. Students often use active coping strategies compared to passive coping strategies.